The Thousand Faces of Virtual Reality - Sik Lanyi, Cecilia (IntechOpen, 2014)
Dr. Cecília Sik Lányi studied Mathematics and Computer Science (M.S.) - József Attila University (1984), and Teacher of Mathematics - Berzsenyi Dániel Teacher Training College in 1988. She obtained the degree of Dr. Univ. at the University of Veszprém, Hungary in Physical-chemistry (1993), and PhD at the University of Veszprém, Hungary in Computer Science (2000). She has worked as a software engineer and as an associate professor for program languages at the University of Pannonia. Currently she is teaching: Virtual Reality and its application, user interface design, and computer graphics for informatics engineering students. PhD and Masters' supervision has an emphasis on Virtual Reality for the rehabilitation of children with disabilities and patients with mental health issues. She got the "Master teacher" award of the Hungarian Ministry of Education in 2001. She has published more than 300 refereed articles and conference papers, and worked as guest editor for many renowned journals and books. Her research area is Virtual Reality, Human Computer Interaction, Design for All. Virtual Reality (VR) has thousand faces. Why? Because from the moment of VR's birth we use it in every field of our life. VR is based on the development of information technology, computer graphics, and strong high speed hardware. VR has high impact not only on research but on our daily living as well. This book has an aim to present applications, trends and newest development in three main disciplines: health sector, education and industry. In this book several new applications are presented in three sections. The first part of the book deals with health care applications. It is followed by a literature review of Augmented Reality (AR). The second section contains industry field education disciplines. The last part shows several industry applications and research. This book will be useful for researchers, engineers and students.